1993
DOI: 10.1002/pssb.2221770203
|View full text |Cite
|
Sign up to set email alerts
|

Shell Structure Potential for Channeling in Solids

Abstract: The position dependence of the stopping power in planar and axial channels using the shell model charge density is established. The corresponding shell atomic potential is derived from the shell charge density using Poisson's equation. By using the continuum model approximation, axial and planar potentials are calculated. A comparison with other frequently used statistical potentials established the possibility to apply this shell potential usefully and analytically to various problems of atomic collisions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The corresponding shell interatomic potential [12] has been derived and extended to both planar and axial cases. It was shown that the shell potential compares well with the other statistical-type potentials [9] in the channeling region (0.1 to 0.2 nm). This gave us the motivation to use this shell potential in channeling radiation studies.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The corresponding shell interatomic potential [12] has been derived and extended to both planar and axial cases. It was shown that the shell potential compares well with the other statistical-type potentials [9] in the channeling region (0.1 to 0.2 nm). This gave us the motivation to use this shell potential in channeling radiation studies.…”
Section: Introductionmentioning
confidence: 84%
“…We have successfully reproduced the z,-oscillations [2] in stopping power for silicon and tungsten for low velocity channeled heavy ions using the shell model charge density [8]. We have also calculated proton energy losses in the intermediate energy region (40 to 300 keV) and a-particle energy losses in the high energy region (0.15 to 18 MeV) in silicon single crystal using the shell model charge density [9] and found the results are in good agreement with experimental results [lo, 111. The corresponding shell interatomic potential [12] has been derived and extended to both planar and axial cases.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here, the calculations have been extended up to the x 6 term. The dependence of the transmission and dechanneling coefficients on the incident beam position have been investigated by using a planar potential function based on the shell structure model [8] and compared with the results of the planar potential function based on Lindhard's model.…”
Section: Introductionmentioning
confidence: 99%